1984
DOI: 10.1136/ard.43.4.599
|View full text |Cite
|
Sign up to set email alerts
|

Non-gouty arthritis in sickle cell disease: report of 37 consecutive cases.

Abstract: SUMMARY Arthritis in association with sickle cell disease was seen in 37 patients in a 2½/2-year period. Cases of gout and of avascular necrosis of the femoral head were excluded. In 12 patients a non-inflammatory effusion occurred during the course of a painful crisis, in 12 patients an ankle effusion occurred in association with spontaneous development or deterioration of leg ulceration, and in 13 patients there was a group of miscellaneous arthritides. Ankle arthritis with leg ulceration has not been previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The first study of rheumatic conditions in a large Jamaican cohort of sickle cell patients was conducted by de Ceulaer et al in 1984, including the review of 1100 SCD records in which the investigators reported four systemic lupus erythematosus patients, one RA, and two patients with chronic non-deforming polyarthritis [5]. In that study the prevalence of RA among SCD patients was 0.27% if non-deforming polyarthritis cases are included.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first study of rheumatic conditions in a large Jamaican cohort of sickle cell patients was conducted by de Ceulaer et al in 1984, including the review of 1100 SCD records in which the investigators reported four systemic lupus erythematosus patients, one RA, and two patients with chronic non-deforming polyarthritis [5]. In that study the prevalence of RA among SCD patients was 0.27% if non-deforming polyarthritis cases are included.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in large Jamaican cohort of 1100 SCD patients reported by de Ceulaer et al in 1984, the prevalence of RA among SCD patients was estimated to be 0.27% if non-deforming polyarthritis cases are included [5]. The musculoskeletal manifestations of SCD including joint involvement might obscure evolving RA among these patients resulting in delayed diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Sympathetic joint effusion results from involved synovium or adjacent bone or marrow. Synovial fluid may be mildly inflammatory, and monoclonal and polyclonal antibodies have been used to identify early leukaemic antigens in the synovial fluid.48 4 However, normal synovial fluid has been found after mononuclear cell infiltration of synovial tissue has already occurred.50 Children do not appear to develop gout, even with high serum urate concentrations,5' but adults do, particularly during treatment. Radiological abnormalities include osteoporosis (fig 4) and osteolysis.…”
Section: Malignant Disorders Ofwhite Cells and Their Precursors Acutementioning
confidence: 99%
“…4 The joints feel warm and tender, and septic arthritis, acute gout, and haemarthrosis should be excluded. Joint aspirate is typically yellow, non-inflammatory, sterile, and free of urate crystals.…”
mentioning
confidence: 99%
See 1 more Smart Citation